SLEEP BRUXISM, FROM ETIOLOGY TO TREATMENT: A LITERATURE REVIEW - de Lima Piccinin Marçal Costa, Bruna; Santello Reginato, Bruno; Thaísa Silva Gargan, Laisla (Health and Society, 2023)
Sleep bruxism is defined as an involuntary habit characterized by the act of clenching and/or grinding teeth. It can occur in two ways: when the patient is awake (wakefulness bruxism) and when he is sleeping (sleep bruxism). Factors such as stress and anxiety are important components in the development of this habit. Problems such as tooth wear, headache, TMD and sleep disorders are among those that are developed by bruxism. There are several forms of treatment, the most common are: occlusal approaches, behavioral approaches, biofeedback and pharmacological approaches. The aim of this study is to discuss the etiology and treatment of sleep bruxism. We used a systematic literature review in the methodology. A computerized search was performed in the PubMed database, using the following keywords: bruxism, sleep disorders, diagnosis and treatment. A total of 212 articles were found, 42 of which included the topic sleep bruxism, etiology and treatment. The results showed that a large part of the population suffers from bruxism, several randomized studies were carried out to find the correct treatment. Among the forms of treatment, the occlusal splint is the most used today and is considered efficient and safe. It is concluded that the diagnosis must be performed by combining a detailed anamnesis, clinical findings, extra and intraoral examination and, mainly, by electromyography and polysomnography examinations , the latter two being considered the gold standard in the diagnosis. New and long studies on sleep bruxism are still needed, as the etiology is still uncertain and the ideal treatment does not yet exist.